ANALISIS HASIL FERMENTASI PEMBUATAN BIOETANOL DENGAN VARIASI MASSA RAGI MENGGUNAKAN BAHAN (BERAS KETAN HITAM, BERAS KETAN PUTIH DAN SINGKONG) - Arry Eko Pristiwanto; Rachmat Subagyo (JTAM ROTARY, 2019)
This study aims to determine the levels of bioethanol from (black sticky rice, white sticky rice and cassava rice) with variations in yeast mass as much as 5 grams, 10 grams and 15 grams knowing the optimum time variation and knowing ethanol levels according to SNI. This research was carried out by hydrolysis or boiling of ingredients (black sticky rice, white sticky rice and cassava rice) using distilled water for 30 minutes, then fermentation using yeast saccharomyces cereviseae and distillation process using a complete destilator to obtain ethanol from fermented then tested with a pen refractometer to determine whether or not ethanol is formed from the distillation process. The selected sample was then tested for ethanol content using a gas chromatography tool. The results of this study are known by testing gas chromatography to find out the ethanol content contained in the distilled sample, the results of ethanol, black glutinous rice with 96 hours fermentation time 92.29% ethanol, and white glutinous rice with fermentation time 96 hours of 100% ethanol and cassava with 96 hours of fermentation time of ethanol content of 98.10%. Keywords: Black Sticky Rice, White Sticky Rice, Cassava, Fermentation, Ethanol